Mixed convection boundary layer flow over a horizontal circular cylinder in a Jeffrey fluid - Zokri, S. M.; Arifin, N. S.; Mohamed, Muhammad Khairul Anuar; Salleh, Mohd Zuki; Mohd Kasim, Abdul Rahman; Mohammad, Nurul Farahain (AIP Publishing, 2017)
In this paper, the mixed convection boundary layer flow and heat transfer of Jeffrey fluid past a horizontal circular cylinder with viscous dissipation effect and constant heat flux is discussed. The governing nonlinear partial differential equations are transformed into dimensionless forms using the appropriate non-similar transformation. Numerical solutions are obtained by using the Keller-box method, which is proven well-tested, flexible, implicit and unconditionally stable. The numerical results for the velocity, temperature, skin friction coefficient and local Nusselt number are attained for various values of mixed convection parameter.